1978
DOI: 10.1111/j.1432-1033.1978.tb20904.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Guanosine 3'-diphosphate 5'-diphosphate in vitro by the spoT Gene Product of Escherichia coli

Abstract: Guanosine 3'-diphosphate 5'-diphosphate (ppGpp) is rapidly degraded to guanosine 5'-diphosphate (ppG) and probably pyrophosphate by an enzyme present in the ribosomal fraction prepared from spoT' strains of Escherichia coli. The ppGpp-degrading enzyme was released from the ribosomes during dissociation at low ionic strength. Ribosomes are not essential for degradation of ppGpp, and decay of ppGpp is strictly dependent on manganese ions. The reaction is sensitive to inhibition by tetracycline, which can be reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…In the presence of pppA, the decay reaction is significantly stimulated and the 3'-pyrophosphoryl group of ppGpp exchanges, displacing the My and ,3 phosphates of pppA. The former reaction is due to a nucleoside diphosphate kinase-dependent reaction that phosphorylates ppG to pppG (21). This finding is in agreement with in vivo data that the rate constant of ppGpp degradation is decreased by an order of magnitude when production of high-energy-containing compounds is blocked (24,25).…”
Section: Resultsmentioning
confidence: 98%
“…In the presence of pppA, the decay reaction is significantly stimulated and the 3'-pyrophosphoryl group of ppGpp exchanges, displacing the My and ,3 phosphates of pppA. The former reaction is due to a nucleoside diphosphate kinase-dependent reaction that phosphorylates ppG to pppG (21). This finding is in agreement with in vivo data that the rate constant of ppGpp degradation is decreased by an order of magnitude when production of high-energy-containing compounds is blocked (24,25).…”
Section: Resultsmentioning
confidence: 98%
“…Notably, Ndx8 produced pGp by sequential hydrolysis of two phosphodiester bonds in ppGpp, whereas pGp and two other intermediates could not be detected from the metabolomics screening in this study. For E. coli, previous in vitro studies reported the activity of (p)ppGpp degradation resulting in the production of pGp, ppGp, and pGpp (9), which are regarded as probable sources for the production of guanosine polyphosphate derivatives in vivo (10,55). Moreover, one of such a product, ppGp, is proposed to act as a strong stringent factor inhibiting purine biosynthesis (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…Heinemeyer and according to [9]; 32P-labeled ppGpp substrates are designated with an asterisk over the 'p'; protein was estimated as in [9].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we have investigated the in vitro degradation of ppGpp in Bacillus stearothermophilus and Bacillus subtilis, in particular we were interested whether ppGpp is degraded by a similar mechanism as has been reported for E. coli [7,8]. In the latter strain a manganese-dependent enzyme has been isolated [9] that released pyrophosphate from the 3'-position of ppGpp yielding ppG [lo].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation